فعالية العلاج العقلاني الانفعالي في تعديل مستوى الصحة النفسية للشباب مدمن على الحشيش - عثماني, نعيمة; رقيق, عبدالله (جامعة الوادي - University of Eloued, 2023)
حضي موضوع الشباب باهتمام كبير من طرف المختصين في جميع الميادين: علم الاجتماع، علم النفس، علم التربية وغيرها نظرا لما تمثله هذه الفئة فهم جزء لا يتجزأ من المجتمع وبنية اساسية فيه، فالشباب في تفاعل ديناميكي تبادلي من حيث التأثير والتأثر في المجتمع. وهذا ما دفعنا للاهتمام بهذه الفئة خصوصا الشباب المدمن على المخدرات وقمنا بتصميم برنامج علاجي خلفيته النظرية تعتمد على العلاج العقلاني الانفعالي السلوكي، اذ يعد أحد أساليب العلاج المعرفي الحديث وضع أسسه ألبرت أليس، وهو نوع من العلاج عن طريق التعليم النشط المباشر، يقوم على أساس بعض الفروض والتعميمات الخاصة بالإنسان وطبيعته، وأسباب تعاسته، واضطرابه الانفعالي، وإمكانات الإنسان وقدرته على التغيير والضبط لمستقبله. وقد انطلقنا من اشكالية مفادها: إلى أي مدى يساهم العلاج العقلاني الانفعالي السلوكي في تحسين مستوى الصحة النفسية لدى الشباب المدمن على الحشيش ؟ وللإجابة على هذه الاشكالية، اعتمدنا على منهج دراسة الحالة ، واستخدمنا للتشخيص محك الدليل التشخيصي الرابع ومقياس الصحة النفسية لعبد المطلب القريطي. واسفرت النتائج على أن هناك تغيير مس الحالة أو ما يعرف بالأثر كان معرفي(تغيير فكرة المخدر هو السند في الحياة) وسلوكي (تجنب أصدقاء يتعاطون المخدرات) انعكس ايجابا على مستوى صحتها النفسية.Abstract: The youth issue has been raised with great interest by specialists in all fields: sociology, psychology, pedagogy, and others, due to what this group represents, as they are an integral part of society and the basic structure in it. Young people are in a dynamic and reciprocal interaction in terms of influence and influence in society. This is what prompted us to pay attention to this group, especially young people addicted to drugs, and we designed a treatment program whose theoretical background is based on rational emotional-behavioral therapy, as it is one of the modern cognitive therapy methods established by Albert Ellis, and it is a type of therapy through direct active education, based on some Assumptions and generalizations pertaining to the human being and his nature, the causes of his unhappiness, his emotional turmoil, and the human potentials and ability to change and control his future. We started from a problem that: To what extent does rational emotional behavior therapy contribute to improving the level of mental health of young people addicted to hashish? To answer this problem, we relied on the case study methodology, and we used for diagnosis the fourth diagnostic manual and the mental health scale of abdelAlmotalib el korayti. The results showed that there was a change in the condition, or what is known as the effect (E). It was cognitive (changing the idea of the drug is the support in life) and my behavior (avoiding friends who use drugs) that reflected positively on the level of her mental health.
مقال
Keywords: الشباب، العلاج العقلاني الانفعالي، الادمان، الحشيش، الصحة النفسية; youth, treatment program, adiction, mental health